Coagulation and Fibrinolysis Activation After Single-Incision Versus Standard Laparoscopic Cholecystectomy: A Single-Center Prospective Case-Controlled Pilot Study. (February 2014) - Zezos, Petros; Christoforidou, Anna; Kouklakis, Georgios; Tsalikidis, Christos; Dimakis, Constantinos; Laftsidis, Prodromos; Virgiliou, Andriana; Simopoulos, Constantinos; Pitiakoudis, Michail
Laparoscopic cholecystectomy is associated with attenuated acute-phase response and hypercoagulable state compared with the open procedure. Single-incision laparoscopic cholecystectomy is a new technique aiming to minimize the invasiveness of the procedure. By comparing the degree of coagulation and fibrinolysis activation after conventional multiport (CLC) and single-incision (SILC) laparoscopic cholecystectomy, we aimed to determine whether the reduced incision size induces a lower thrombophilic tendency. Thirty-two adult patients with noncomplicated symptomatic cholelithiasis were nonrandomly assigned to CLC or SILC. Prothrombin fragment 1 + 2 (F1 + 2), thrombin–antithrombin complexes (TAT), D-dimers, fibrinogen, and von Willebrand factor levels were measured at baseline, at 1st, and 24th hour, postoperatively. Twenty-six patients were finally included in the study. Fifteen patients underwent CLC (male/female: 5/10) and 11 underwent SILC (male/female: 1/10). There were no perioperative complications. An almost similar postoperative pattern and degree of activation of coagulation and fibrinolysis pathways was noted in both groups. No statistically significant differences were found between SILC and CLC for F1 + 2, TAT, D-dimers, fibrinogen, and von Willebrand factor levels, duration of surgery, length of hospital stay, and postoperative morbidity. A similar pattern and extent of coagulation and fibrinolysis activation is present in SILC and CLC, and therefore there is no difference in tendency for thrombosis. Thromboembolic prophylaxis should be considered in SILC as recommended for CLC, pharmacologic or mechanical, considering the hemorrhagic risk and the presence of additional thromboembolism risk factors. SILC appears to be a safe, feasible technique that can be recommended for its potential advantages in cosmesis and reduced incisional pain.